Clostridium difficile Infections amongst Patients with Haematological Malignancies: A Data Linkage Study - Selvey, Linda; Slimings, C.; Joske, D.; Riley, T. (Public Library of Science, 2016)
OBJECTIVES: Identify risk factors for Clostridium difficile infection (CDI) and assess CDI outcomes among Australian patients with a haematological malignancy. METHODS: A retrospective cohort study involving all patients admitted to hospitals in Western Australia with a haematological malignancy from July 2011 to June 2012. Hospital admission data were linked with all hospital investigated CDI case data. Potential risk factors were assessed by logistic regression. The risk of death within 60 and 90 days of CDI was assessed by Cox Proportional Hazards regression. RESULTS: There were 2085 patients of whom 65 had at least one CDI. Twenty percent of CDI cases were either community-acquired, indeterminate source or had only single-day admissions in the 28 days prior to CDI. Using logistic regression, having acute lymphocytic leukaemia, neutropenia and having had bacterial pneumonia or another bacterial infection were associated with CDI. CDI was associated with an increased risk of death within 60 and 90 days post CDI, but only two deaths had CDI recorded as an antecedent factor. Ribotyping information was available for 33 of the 65 CDIs. There were 19 different ribotypes identified. CONCLUSIONS: Neutropenia was strongly associated with CDI. While having CDI is a risk factor for death, in many cases it may not be a direct contributor to death but may reflect patients having higher morbidity. A wide variety of C. difficile ribotypes were found and community-acquired infection may be under-estimated in these patients.